From Protoclusters to Clusters: The Role of Large-Scale Structure in Galaxy Evolution - Gully, Harry (2025)
This thesis explores the impact of environment on galaxy evolution at high redshift, focusing on the role of environmental quenching in clusters and protoclusters. By combining deep observational data from multiple surveys with statistical analyses, this work investigates how dense environments influence galaxy star formation, mass assembly, and quenching across cosmic time. Two central questions are addressed: (1) Do the mechanisms that quench galaxies in cluster environments in the local Universe operate in the same way – or at all – in higher redshift clusters and protoclusters? (2) How do different detection methods affect samples of protoclusters and influence the derived conclusions about quenching in dense environments?